The effectiveness of storytelling in improving language literacy in children aged 5–6 years to support primary school readiness - Yesi Novitasari; Efastri Sean Marta; Suharni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study examines the effect of storytelling on the language and literacy skills of children aged 5–6 years, as a foundation for school readiness. Language literacy is an essential component of school readiness because it supports children's ability to understand instructions, communicate effectively, participate in classroom interactions, and engage in early learning activities when entering primary school. However, numerous preschool children still experience difficulties with listening, speaking, vocabulary, retelling, early reading, and early writing. Therefore, effective learning strategies are needed to strengthen children's language literacy before transitioning to formal education. This study employs a quasi-experimental, non-equivalent control group design. The participants consisted of 20 children aged 5–6 years from TK Negeri Pembina V Pekanbaru, divided into an experimental group (n = 10) and a control group (n = 10). Data were collected using an observation sheet comprising 18 items covering six language literacy indicators: listening, speaking, vocabulary, retelling, early reading, and early writing. The experimental group received storytelling-based instruction, while the control group participated in conventional learning activities. Data were analyzed using descriptive statistics and an independent-samples t-test after confirming the assumptions of normality and homogeneity. The results reveal that the experimental group achieved a substantially higher mean score (M = 78.50, SD = 3.37) than the control group (M = 31.00, SD = 5.16). The Independent Samples t-test indicates a statistically significant difference between the two groups (t = -24.349, p < .001), demonstrating that storytelling had a significant positive effect on children's language literacy development. The findings underscore that storytelling is a potentially effective pedagogical strategy for developing language literacy and strengthening school readiness in early childhood education.